On the Use of 1-bit DACs in Massive MIMO Systems - Guerreiro, João (2017)
Massive multiple-input multiple-output (MIMO) systems are being proposed for next generation broadband wireless systems. However, as the complexity of implementation grows with the number of antenna elements, their feasibility is a challenging task. Consider very low complexity, 1-bit digital-to-analogue converters (DACs) for the downlink of massive MIMO systems. The impact of the resultant severe non-linear distortion effects is analysed when a low-complexity maximum ratio transmission technique is employed for user separation. The non-linear distortion levels decrease with the number of transmit antennas allowing good performance, even with 1-bit DACs are shown.